Evaluation of Insecticidal Activity of Tanacetum parthenium Plant against Housefly (Musca domestica) in Bojnord, Iran: Evaluasi Aktivitas Insektisida Tanaman Tanacetum parthenium terhadap Lalat Rumah (Musca domestica) di Bojnord, Iran - Fatemeh Kouhestani; Mohammad Saaid Dayer; Hassan Vatandoost; Kourosh Arzamani; Hossein Kamali; Mehdi Imani; Ameneh Mohammadi (Indonesian Journal on Health Science and Medicine, 2025)
General Background Botanical insecticides are increasingly explored as alternatives to synthetic chemicals due to rising resistance in medically important pests. Specific Background Tanacetum parthenium is a medicinal plant rich in pyrethrins and traditionally known for multiple pharmacological properties, yet its bioactivity against Musca domestica had not been tested. Knowledge Gap No previous experimental data existed on the toxicity of feverfew extracts against larval and adult houseflies from North Khorasan, Iran. Aims This study aimed to extract active ingredients from wild T. parthenium and evaluate their insecticidal activity against larvae and adults of M. domestica. Results Bioassays showed dose- and time-dependent mortality in both life stages, with LC50 and LC90 values of 5135 and 8840 ppm for adults at 48 h, and 329 and 551 ppm for larvae at 24 h, indicating higher susceptibility in larvae. Novelty This is the first report demonstrating the insecticidal properties of T. parthenium against houseflies under controlled laboratory conditions. Implications The findings indicate that native feverfew extracts could serve as a botanical bio-insecticide for vector and pest control, supporting environmentally friendly alternatives to synthetic insecticides. Keywords: Tanacetum Parthenium, Musca Domestica, Botanical Insecticide, Pyrethrins, Bioassay Key Findings Highlights: Feverfew extracts caused strong dose-dependent mortality in both developmental stages. Juvenile forms required much lower concentrations than mature forms. Pyrethrin-containing fractions were responsible for toxic action.